The Impact of WhatsApp on EFL Learners’ Reading Skills: A Narrative Literature Review - Abdul Rasheed Soomro; Sarala Thulasi Palpanadan (Development in Language Studies, 2024)
This review synthesizes existing research on the impact of WhatsApp on EFL (English as a Foreign Language) learners’ reading skills. Employing a systematic approach, the study utilizes journal articles retrieved from databases like ScienceDirect and Google Scholar, focusing on publications between 2019 and 2024. Relevant keywords like "technology in EFL classrooms" and "WhatsApp for language learning" guided the search process. The snowballing technique further enriched the literature pool by examining references from identified articles. The review underscores WhatsApp’s potential to enhance EFL reading comprehension. Studies demonstrate its effectiveness in promoting reading engagement and improving comprehension scores. Building upon these insights, the review suggests future research directions. These include investigating the specific mechanisms by which WhatsApp and similar platforms contribute to learning outcomes, exploring its effectiveness for different learner demographics, and examining potential drawbacks like information overload and distractions. Finally, the review emphasizes the need to develop best practices for integrating WhatsApp into EFL reading instruction, providing educators with guidelines on content selection, fostering meaningful interactions, and ensuring academic integrity.